Value Management: A Systematic Approach for Improving Time Performance in Construction Projects - Nasir, Najuwa; Mohd Nawi, Mohd Nasrun; Zulhumadi, Faisal; Anuar, Herman Shah; Radzuan, Kamaruddin (International Journal of Supply Chain Management, 2016)
The construction industry is considered to be the largest contributor to the nations economy. However, there are many challenges that had to be overcome to ensure construction projects are successful in achieving the minimum cost to utilize the necessary resources in the success of the project. Some of the construction projects failed to be completed on schedule due to the negligence of certain parties in ensuring that the project value is at the maximum level. Responding to the challenge, this research hopes to counter this problem and help towards the betterment of the construction industry using a value management approach. Therefore, this paper discusses the successful factors in implementing value management through the interview and documentation data gathering process. As a result, it shows that local practitioners of value analysis in construction projects should consider these important factors as a catalyst for increasing the value of projects.